Transcriptome and Coexpression Network Analyses Provide Insights into the Resistance of Chinese Cabbage During Different Stages of Plasmodiophora brassicae Infection - Huishan Liu; Lili Wang; Guozheng Wang; Haidong Wu; Xin Wang (Plants, 2025)
Clubroot is a destructive soilborne disease caused by Plasmodiophora brassicae that threatens the production of Chinese cabbage. The molecular mechanisms underlying the resistance of Chinese cabbage to clubroot remains unclear, making the identification and analysis of resistance genes crucial for developing resistant varieties. Comparative transcriptome analysis of roots from the resistant line “JJ S5-1” and the susceptible line “SYY10-1” revealed significant differences in gene expression profiles at various stages after inoculation. Weighted gene coexpression network analysis revealed midnight blue and green modules as substantially associated with disease response, with each showing positive regulatory patterns. Several defense-related genes and transcription factors important for resistance to Plasmodiophora brassicae were identified, including disease resistance proteins, PR1, PBS1, and TGA, and WRKY transcription factors, most of which were upregulated following inoculation. Key genes associated with trait-related expression patterns were analyzed and a working model was proposed to explain the mechanism of clubroot disease resistance to Plasmodiophora brassicae infection in Chinese cabbage. These findings offer a valuable resource for further investigation of the immune response in the resistance of “JJ S5-1” to clubroot disease.